Часо-простір японських дзуйхіцу та «сполохів» Костя Москальця - Колесникова, Любов; Kolesnykova, Lubov (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті здійснено порівняння часо-просторів японських мініатюр дзуйхіцу та «сполохів» К. Москальця. Приділено увагу соціально-політичним, філософським та естетичним чинникам, що сприяли появі цього жанру в середньовічній Японії і його поширенню в українській літературі 80–90-х рр. In article are compared chronotopes of Japanese miniatures zuihitcu and lightnings in the work of Kost’ Moskalets «The Cell of Tea Rose. 1989−1999». It is established that they have in common is the composition method of creation of works from the separate miniatures united by the identity of the author, with frequent change of plans and transitions from high to ordinary. However for zuihitcu the linear principle of connection of miniatures, and for «lightnings» − concentric is characteristic. In the article Attention is paid to the socio-political, philosophical, and aesthetic factors which promote emergence of this genre in medieval Japan and its distribution in the Ukrainian literature 80−90 years.
Chronotopes of Japanese Zuihitcu and «Lightnings» of Kost’ Moskalets
Keywords: дзуйхіцу; zuihitcu; «сполохи»; «lightnings»; часо-простір; chronotope; ДАК; DAK; Кость Москалець; Kost’ Moskalets